3D FEM analyses of the ultrasonic transducer for controlled nanowire rotary driving. (February 2016) - Wang, Xiaofei; Hu, Junhui
Highlights: The transducer for NW rotary driving is analyzed by 3D FEM. The stability is influenced by the vibration transmission strip's size. The manipulating probe's size should be properly designed to avoid its resonance. Abstract: Controlled rotary driving of single nano objects is an important technology in the assembling of nano structures, handling of biological samples, nano measurement, etc. However, there have been little analyses on the ultrasonic transducers for the nano rotary driving, which makes the transducer's optimization impossible. In this work, vibration characteristics of the ultrasonic transducer for rotary driving of single nanowires, which has been proposed by the authors' group, are analyzed by the 3D finite element method (FEM), and some useful guidelines for designing the transducer are achieved. It is found that the working point still exists when the commonly used metal materials in ultrasonic transducers are used as the vibration transmission strip, and when the vibration transmission strip's size changes. It is also found that the direction of the elliptical motion of the micro manipulating probe's tip may be reversed by changing the size of the vibration transmission strip properly. In addition, to ensure the performance consistency of the device, the micro manipulating probe's length Lm or driving frequency should be designed to avoid the resonance of the micro manipulating probe.